Vulnerability and Poverty Cycle of Child Labor in the Urban Informal Sector: A Case Study of Kramat Jati Wholesale Market, Jakarta - Ginting, Septa Novasari; Barus, Sri Hernita (ARISTO, 2025)
The phenomenon of child labor, especially for women in the urban informal sector, is still a complex social problem in Indonesia. This study aims to analyze the factors that encourage girls to work in the informal sector, the impact of work on their welfare, and the effectiveness of government policies in addressing this problem. Using a qualitative approach and case study method at the Kramat Jati Wholesale Market, Jakarta, this study collected data through field observations, in-depth interviews with girl workers and their families, and policy analysis related to child labor in Indonesia. The study results indicate that family poverty, lack of access to education, and social norms normalizing child labor are the main factors that encourage them to work. These girl workers are socially excluded in various forms. The lack of inclusive education services for children of workers is intertwined with them losing access to other rights such as poor health conditions, lack of safe places, vulnerable families due to crime and  unregistered marriages, dropping out of school, and ending child marriage. Educational inequality perpetuates child labor and creates a cycle of poverty that is passed down to the next generation.